Digital literacy and academic performance: the mediating roles of digital informal learning, self-efficacy, and students’ digital competence - Zakir, Supratman; Hoque, Mohammad Enamul; Susanto, Perengki; Nisaa, Verselly; Alam, Md. Kausar; Khatimah, Husnil; Mulyani, Erly (Frontiers in Education, 2025)
The rapid evolution of digital technology has significantly influenced learning systems. Digital technology serves as a catalyst for transformative shifts in the manner in which individuals engage in many activities including educational pursuits. The widespread use of digital technology throughout all sectors, including education, has served as a catalyst for students to embrace and utilize new technology. However, challenges arise with the incorporation of digital technology into the classroom. This study investigated the relationship between digital literacy and academic performance, taking into account the role of digital informal learning, self-efficacy, and students’ digital competence as mediators. This study utilized a quantitative methodology employing a structured questionnaire for data collection and Structural Equation Modeling (SEM) for hypothesis testing. This study found that improving students’ digital literacy skills can lead to thriving in academic pursuits. The empirical findings demonstrate that an increase in digital literacy improves digital competence, informal digital learning engagement, and digital self-efficacy. Additionally, possessing digital competence, engaging in digital informal learning, and having digital self-efficacy increases the likelihood of academic success. Therefore, digital competence, digital informal learning, and digital self-efficacy serve as partial mediators in the relationship between digital literacy and academic success. Hence, possessing digital competence, engaging in digital informal learning, and having digital self-efficacy contribute to enhancing the influence of digital literacy on academic achievement. These findings offer insightful implications for educators and policymakers.